The Impact of Technology Acceptance on Satisfaction in Receiving Services at the Educational Service Center, North-Chiang Mai University - ปิงพยอม ลลิตา; คำขันแก้ว พงศ์ศิริ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
In the era where Information and Communication Technology (ICT) plays a crucial role in the development of education, higher education institutions must adapt by integrating technology into their management and educational service delivery to enhance efficiency. North-Chiang Mai University has developed the NCU Eagle Soft (NES) system to provide comprehensive educational services. This study aimed to investigate the influence of perceived usefulness, ease of use, and user attitude on students’ satisfaction with the educational service center of North-Chiang Mai University. Data were collected through questionnaires from a sample of 165 participants and analyzed using statistical methods to test the research hypotheses. The results revealed that perceived usefulness and ease of use had a statistically significant influence on service satisfaction, with standardized regression coefficients of 0.502 and 0.277, respectively, while attitude toward use did not show a significant influence. These findings highlight the importance of designing service systems that prioritize user benefits and convenience. The results can serve as a guideline for other higher education institutions in developing effective digital service systems in the future.